Increased INR Values Predict Accelerating Deterioration and High Short-Term Mortality Among Patients Hospitalized With Cirrhosis or Advanced Fibrosis - Ying Wang (Frontiers Media S.A., 2021)
Background and Objective: An increase in the international normalized ratio (INR) is associated with increased mortality in patients with cirrhosis and other chronic liver diseases, while little is known about the quantitative relationship. This study aimed to investigate the quantitative relationship between the INR and short-term prognosis among patients hospitalized with cirrhosis or advanced fibrosis and to evaluate the role of the INR as a risk factor for short-term liver transplant (LT)-free mortality in these patients.Patients and Methods: This study prospectively analyzed multicenter cohorts established by the Chinese Acute-on-Chronic Liver Failure (CATCH-LIFE) study. Cox regression was used to describe the relationship between the INR and independent risk factors for short-term LT-free mortality. Forest plots were used in the subgroup analysis. Generalized additive models (GAMs) and splines were used to illustrate the quantitative curve relationship between the INR and the outcome and inflection point on the curve.Results: A total of 2,567 patients with cirrhosis and 924 patients with advanced fibrosis were included in the study. The 90-day LT-free mortality of patients with cirrhosis and advanced fibrosis was 16.7% (428/2,567) and 7.5% (69/924), respectively. In the multivariable Cox regression analysis, the increase in the INR was independently associated with the risk of 90-day LT-free mortality both in patients with cirrhosis (HR, 1.06; 95% CI, 1.04–1.07, p < 0.001) and in patients with advanced fibrosis (HR, 1.09; 95% CI, 1.06–1.12, p < 0.001). An INR of 1.6/1.7 was found to be the starting point of coagulation dysfunction with a rapid increase in mortality in patients with cirrhosis or in patients with advanced fibrosis, respectively. A 28-day LT-free mortality of 15% was associated with an INR value of 2.1 in both cirrhosis and advanced fibrosis patients.Conclusions: This study was the first to quantitatively describe the relationship between the INR and short-term LT-free mortality in patients with cirrhosis or advanced fibrosis. The starting points of INR indicating the rapid increase in mortality and the unified cutoff value of coagulation failure in cirrhosis and advanced fibrosis, will help clinicians accurately recognize early disease deterioration.